Barnets beste Rettighetens innhold i saker om opphold på humanitært grunnlag og utvisning - Martnes, Mona (Scandinavian University Press (Universitetsforlaget), 2021)
The author examines the contents and function of the right of the child to have his or her best interests taken as a primary consideration in expulsion cases and cases concerning residence permit on humanitarian grounds in Norway. This right is articulated in Article 3 no. 1 of the United Nations Convention on the Rights of the Child (CRC) and Section 104 (2) of the Norwegian Constitution. The right applies in "all actions concerning children", and in cases concerning expulsion and residence permits on humanitarian grounds. The author investigates when and how the best interests of the child can give a child and its nearest family a right to stay in Norway. It contains a thorough analysis of sources from the United Nations Committee on the Rights of the Child and judgments from the Supreme Court of Norway and the European Court of Human Rights.